FORMATION OF PLAN COST OF READY PRODUCTS OF STEEL PRODUCTION RUP «BMZ» BY MEANS OF MODULE CONTROLLING OF SYSTEM SAP R/3 - S. N. Astratov (Литьë и металлургия)
It is shown that formation of the planned cost price of finished goods of steel production of RUP«BMZ»by mean of the module of controlling system SAPR/3 – one of the most effective administrative tools at the current stage of market relations.